Lab-Scale Thermal Decomposition of Hydrogen Peroxide as Green Propellant over Low-Cost Catalysts Based on Copper Deposited on Different Supports - Imane Remissa; Ahmed E. S. Nosseir; Amit Tiwari; Ahmed Bachar; Assia Mabrouk; Rachid Amrousse (Aerospace)
The thermal decomposition of hydrogen peroxide (H2O2) as a promising green propellant was performed over free-noble metallic-based catalysts deposited on abundant supports. A 30% (w/w) H2O2 liquid was decomposed over 1 wt.% of copper-based catalysts deposited on three different supports: γ-alumina, graphite and monocrystal clay. In this research work, the catalytic performance of the thermal decomposition of H2O2 was carried out by measuring the differential pressure (ΔP) versus time at initial constant temperatures and, for the first time, by the DTA-TG technique and by the DIP-MS technique at atmospheric pressure. The obtained preliminary results showed that copper deposited on alumina and on graphite are promising catalysts for the decomposition of the H2O2 liquid propellant. Moreover, the natural clay can be valorized on the thermal decomposition of H2O2 due to its high resistivity and high surface area. The N2-physisorption technique and scanning electron microscopy technique were used to characterize the effect of the texture properties on the decomposition and to understand the morphological characteristics of the catalyst.